Quality of sleep in hemodialysis patients: the role of demographic and clinical characteristics - Aljušević, Sena M; Vatić, Mirela; Trbojević- Stanković, Jasna (Medicinski podmladak, 2017)
Conclusion: The type of dialysis treatment and dialysis shift are closely interrelated with the quality of sleep in patients on chronic HD treatment. Introduction: Sleep disorders are common among patients treated with chronic dialysis. Still, these conditions are seldom diagnosed and often undertreated, because they are attributed to the renal disease itself and/or considered a reaction to dialysis treatment. Objective: The aim of this study was to assess the prevalence of poor sleep quality and its relations with demographic and clinical characteristics of patients undergoing chronic hemodialysis (HD). Material and Methods: A cross-sectional observational study was performed on 82 patients (49 men, mean age 64.77 ± 10.00 years, range 30-85) on maintenance HD in a University Hospital Center in Belgrade. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI). Other relevant data were collected by general questionnaire and from patients’ medical histories. Data were analyzed with Chi-square, Fisher and T test, using the SPSS (version 21.0). Results: The mean PSQI was 6.74 ± 3.99. Poor quality of sleep (PSQI>5) was present in 47 (57.3%) patients. Patients treated with hemodiafiltration statistically significantly more often had better quality of sleep (p=0.047), whereas patients receiving dialysis treatment in the afternoon shift had significantly more frequently poor quality of sleep (p=0.017). Age, sex, employment status, comorbidities, dialysis vintage and adequacy were not significantly related to the quality of sleep. Key words: quality of sleep, dialysis, hemodialysis